Penerapan Konsep Ekologis untuk Pendidikan Lingkungan pada “Taman Pintar” di Kelurahan Kayu Putih, Jakarta Timur - Qurrotu ‘Aini Besila; Astrid Widiasari Kusumadewi (Universitas Sebelas Maret, 2018)
Taman Pintar with area of 3.104 m2 located in Waringin Raya street, Kayu putih, Pulo Gadung, East Jakarta. This park is located in a crowded settlement area that is burdened by social and environmental issue, one which emerge as a place for illegal drug and alcohol transaction, a landfill for debris and trash, even flooding in times of rain. Starting from empty field with fences of precast that is not treated and abandoned, this land that is owned by the government of DKI Jakarta change drastically into a green open space that is loaded with unexpected benefits since build into a Taman Pintar in 2015. Filled with various children playground facilities, sport facilities, and miniature of urban forest, Taman Pintar became a social interaction room for the local community and possesses high ecological functions. This park has a huge basin underneath its plaza, five infiltration wells, and thirty biopori pits which is made the surrounded area of the park no longer flooded in rainy season. This study aims to examine the ecological concept of the design and construction of Taman Pintar. This paper used a qualitative descriptive method, the result shows when the consideration of ecology turned into a priority in the park design, this will give an opportunity to make the development of the park has more benefit on ecological side that gives positive impacts, moreover the addition of facilities also capable to increase the ecological value of the park. The result is expected to be a recommendation for other parks development in Jakarta which can be maximized to become a great environmental education facilities for the local communities.